The perception of fairness in the division of labor around first childbirth in Germany - Maria Hornung; Chiara Ludovica Comolli (Genus)
Abstract The transition to parenthood is a pivotal life course event that impacts well-being, relationship quality and the distribution of housework and paid work. In Germany, during the transition to first-time parenthood, women often reduce their involvement in paid work and take on a larger share of housework, leading to a more gendered division of labor. This shift could influence perceptions of fairness in the division of labor inducing both men and women to perceive the division as being more fair to themselves or more fair to their partner. Using data from the German Panel Analysis of Intimate Relationships and Family Dynamics (pairfam) and fixed effects models, we examine how women’s and men’s perception of fairness of the division of labor varies around first childbirth conceptualizing different phases spanning from 5 years before until 5 years after the first childbirth. Relative to baseline, mothers (-to-be) reported a fairer division of labor (less under-benefitting) from around conception to right after childbirth. Yet, already from 6 months after childbirth mothers’ perception of fairness becomes less fair to them again and the perception of under-benefitting continues as the child ages. For fathers-to-be, perceptions of fairness did not vary substantially around childbirth. We further found that neither the change in the division of housework, nor in the division of paid work, explained changes in fairness perceptions during the transition to parenthood.